Parental Reflective Functioning: Theory, Research, and Clinical Applications. Issue 1 (31st March 2017) - Luyten, Patrick; Nijssens, Liesbet; Fonagy, Peter; Mayes, Linda C.
ABSTRACT: This paper reviews recent theoretical, empirical, and clinical work related to parental reflective functioning (PRF) or parental mentalizing. PRF refers to the capacity of the parent to envision his or her child as being motivated by internal mental states such as feelings, wishes, and desires, and to be able to reflect on his or her own internal mental experiences and how they are shaped and changed by interactions with the child. This paper first briefly discusses the historical and theoretical background of this concept and its purported role in child development, with a focus on the development of child attachment, affect regulation, and mentalizing. It then reviews recent thinking and research in four areas: (1) the neurobiology underlying PRF, (2) the multidimensionality of PRF, (3) the relationship between PRF and trauma, and (4) the broader relevance of attention to internal mental states for the development of epistemic trust as the basis of an evolutionary inbuilt capacity for learning from and within social communication. It closes with a brief review of the background of, and empirical evidence supporting, interventions rooted in theoretical considerations concerning the importance of PRF, as well as suggested directions for future research and clinical practice.